Transforming Fe-Cu alloys with unprecedented BCC Cu precipitates toward dual mechanical functionalities - Jeong Rae Kim; Hyun-Su Kang; Tae-Wan Ko; Young Jae Hwang; Gun Hee Kim; Seon-Jin Choi; Kwangchoon Lee; Hyuk-Su Han; Hyung Giun Kim; Taeg Woo Lee (Materials & Design)
An Fe-10Cu alloy was fabricated without internal defects using a powder metallurgy-hot isostatic pressing (PM-HIP) method under high pressure conditions to determine the changes in its microstructure and physical properties according to the sintering temperature. In general, Cu precipitates in Fe-Cu alloys have been observed in an FCC structure, and studies on BCC Cu precipitates smaller than 6 nm have only been theoretically reported. However, for the first time, we found that Cu precipitates with a BCC structure larger than 50 nm may occur in an Fe-Cu alloy. An Fe-Cu alloy containing BCC Cu precipitates in a fully coherent relationship with the α-Fe matrix was observed to have completely different brittle fracture mode, along with higher tensile strength and thermal conductivity compared to an Fe-Cu alloys containing FCC Cu precipitates.